2012
DOI: 10.1016/j.bpj.2012.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Binding of β-Amyloid (1–42) Peptide to Negatively Charged Phospholipid Membranes in the Liquid-Ordered State: Modeling and Experimental Studies

Abstract: To explore the initial stages of amyloid β peptide (Aβ42) deposition on membranes, we have studied the interaction of Aβ42 in the monomeric form with lipid monolayers and with bilayers in either the liquid-disordered or the liquid-ordered (L(o)) state, containing negatively charged phospholipids. Molecular dynamics (MD) simulations of the system have been performed, as well as experimental measurements. For bilayers in the L(o) state, in the absence of the negatively charged lipids, interaction is weak and it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
103
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(113 citation statements)
references
References 60 publications
10
103
0
Order By: Relevance
“…A vast number of human diseases are associated with protein misfolding and extracellular formation of highly organized aggregates with fibrillar morphology (Ahyayauch et al, 2012). Evidence shows that short peptides are involved in regulating the proper folding of proteins, which implicates the possible role of peptides in prevention of amyloid fibrilogenesis.…”
Section: Inhibition Of Amyloid Fibril Formationmentioning
confidence: 99%
See 3 more Smart Citations
“…A vast number of human diseases are associated with protein misfolding and extracellular formation of highly organized aggregates with fibrillar morphology (Ahyayauch et al, 2012). Evidence shows that short peptides are involved in regulating the proper folding of proteins, which implicates the possible role of peptides in prevention of amyloid fibrilogenesis.…”
Section: Inhibition Of Amyloid Fibril Formationmentioning
confidence: 99%
“…Antioxidant peptides, aside from their nutritional benefits, can suppress the oxidation reactions through various mechanisms including inactivation of reactive oxygen species, free radicals scavenging, chelation of pro-oxidative transition metals and promoting the enzymatic elimination of specific oxidants (Bamdad, Wu, & Chen, 2011). In a related area of research, free radical reactions are shown to be the critical step in amyloid fibril formation (Ahyayauch et al, 2012). Normal cell functions are disturbed by the aberrant aggregation of proteins leading to highly ordered protein assemblies such as amyloid fibrils (Gazit, 2005).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…As such, this short transmembrane segment is often used in studies of the protein interactions and partitioning in the membrane [47,48]. While A peptides are frequently reported in an extracellular location, A 1-40 and A 1-42 molecules were found to strongly interact with negatively charged lipids and to bind to anionic, negatively charged membranes [49][50][51][52][53][54][55], orienting parallel to the membrane surface. Through X-ray and neutron diffraction, Mason et al [56] and Dante, Hauß and Dencher [47] observed an embedded state for the A 25-35 segment and the full-length A 1-42 peptide in anionic lipid membranes [57].…”
Section: Position Of Amyloid-peptides In Lipid Membranesmentioning
confidence: 98%